DermACELL Acellular Dermal Matrix in Oncologic Breast Reconstruction: A Cohort Study and Systematic Review. Issue 6 (20th June 2022) - Swisher, Austin R.; Landau, Mark J.; Kadakia, Nikita; Holzmer, Stephanie W.; Kim, Hahns Y.
Abstract : Background: Acellular dermal matrices (ADMs) are commonly used in tissue expander and direct-to-implant reconstruction following mastectomy. Few studies have reported outcomes of DermACELL use or compared DermACELL with AlloDerm ADM. This study sought to compare outcomes of DermACELL and AlloDerm in oncologic breast reconstruction and to review the literature reporting outcomes of patients undergoing reconstruction using DermACELL. Methods: We conducted a retrospective cohort study to compare outcomes between DermACELL and AlloDerm ADM, and a systematic review of the literature with a meta-analysis to evaluate clinical outcomes with DermACELL. Results: Seventy-four patients (128 breasts) undergoing immediate reconstruction were evaluated retrospectively. Chi-square analysis revealed no significant difference in postoperative outcomes between the two groups. Our systematic review of the literature yielded 12 total studies reporting DermACELL use for breast reconstruction encompassing 518 patients and 608 total breasts. A pooled analysis of the published data did not reveal a significant change in the rate of explantation when either chemotherapy or radiation was used. Meta-analysis did not show a significant difference in the rate of any of the complications evaluated. Conclusion: DermACELL is safe to use with a relatively consistent complication profile as compared with AlloDerm.